2015
DOI: 10.1111/jdv.13167
|View full text |Cite
|
Sign up to set email alerts
|

Is an online skin cancer toolkit an effective way to educate primary care physicians about skin cancer diagnosis and referral?

Abstract: The skin cancer toolkit is an accessible online learning resource for improving confidence with skin cancer referral amongst GPs. Although we were unable to identify any immediate changes in skin cancer diagnoses or appropriate referral behaviours, research is required to evaluate its longer term effects on outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 26 publications
0
34
1
1
Order By: Relevance
“…Likewise, three other intervention studies found that use of a CET did not reduce referrals to dermatology [ 13 , 32 , 33 ]. While reduction of referrals and other return appointments may be a clinical goal to save patient and provider time and to reduce costs, its attainment through usage of CETs has not been established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, three other intervention studies found that use of a CET did not reduce referrals to dermatology [ 13 , 32 , 33 ]. While reduction of referrals and other return appointments may be a clinical goal to save patient and provider time and to reduce costs, its attainment through usage of CETs has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatology is an area of concern in primary care for which previous literature extensively discusses the goals of improving diagnostic accuracy, improving the management of skin disease, and reducing referrals [ 8 12 ]. Some studies in primary care and hospital settings show that a dermatology education tool kit [ 13 ] and diagnostic support CET [ 14 ] can improve provider confidence and diagnostic accuracy. However, few studies have examined the impact of a single CET on provider practice or patient outcomes from the provider's perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have examined the benefits of online learning modules for medical students as well as residents. [9][10][11][12][13] Online learning modules are an effective, preferred method of learning for providers of all educational levels. 14,15 The American Academy of Dermatology has developed 18 online learning modules focused on core competency and needs assessments of primary care physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Better educated providers and a streamlined data collection system may encourage the use of teledermatology as well as reduce the number of unnecessary face‐to‐face consultations. Multiple studies have examined the benefits of online learning modules for medical students as well as residents . Online learning modules are an effective, preferred method of learning for providers of all educational levels .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicate that additional dermatology knowledge, training, and diagnostic support could improve practice and patient outcomes. General practitioners in the United Kingdom who used an online source for skin cancer diagnosis information increased their diagnostic accuracy and confidence, but referrals were not reduced [16]. Referrals to dermatology in a Veterans Affairs hospital that lacked a specific diagnosis were reduced by an intervention that trained PCPs [17].…”
Section: Introductionmentioning
confidence: 99%